Investigation of Clostridium botulinum group III's mobilome content. (February 2018) - Woudstra, Cédric; Le Maréchal, Caroline; Souillard, Rozenn; Anniballi, Fabrizio; Auricchio, Bruna; Bano, Luca; Bayon-Auboyer, Marie-Hélène; Koene, Miriam; Mermoud, Isabelle; Brito, Roseane B.; Lobato, Francisco C.F.; Silva, Rodrigo O.S.; et al.
Abstract: Clostridium botulinum group III is mainly responsible for botulism in animals. It could lead to high animal mortality rates and, therefore, represents a major environmental and economic concern. Strains of this group harbor the botulinum toxin locus on an unstable bacteriophage. Since the release of the first complete C. botulinum group III genome sequence (strain BKT015925), strains have been found to contain others mobile elements encoding for toxin components. In this study, seven assays targeting toxin genes present on the genetic mobile elements of C. botulinum group III were developed with the objective to better characterize C. botulinum group III strains. The investigation of 110 C. botulinum group III strains and 519 naturally contaminated samples collected during botulism outbreaks in Europe showed alpha-toxin and C2-I/C2-II markers to be systematically associated with type C/D bont- positive samples, which may indicate an important role of these elements in the pathogenicity mechanisms. On the contrary, bont type D/C strains and the related positive samples appeared to contain almost none of the markers tested. Interestingly, 31 bont -negative samples collected on farms after a botulism outbreak revealed to be positive for some of the genetic mobile elements tested. This suggests loss of the bont phage, either in farm environment after the outbreak or during laboratory handling. Highlights: Mobilome content of C. botulinum group III strains and samples were evaluated. Mobile elements p2 and p3 were systematically associated with bont type C/D. Bont type D/C showed to contain very few mobile elements. 31 bont negative environmental samples were tested positive for typical C. botulinum group III mobile elements.